First case of human anisakiasis in Poland. (June 2020) - Kołodziejczyk, Lidia; Szostakowska, Beata; Sobecka, Ewa; Szczucki, Krzysztof; Stankiewicz, Kamil
Abstract: Consumption of raw or inadequately processed marine fish may result in anisakidosis – a zoonotic disease caused by larvae of the parasitic nematodes of the family Anisakidae (anisakiasis when caused by members of the genus Anisakis (Nematoda: Anisakidae)), commonly found in a variety of marine fish species all over the world. Most cases of anisakidosis have been detected in the residents of Japan and South Korea, which results from the tradition of eating raw and semi-raw fish dishes. However, the disease is now increasingly often diagnosed in other parts of the world, including Europe (mainly in Spain and Italy). In Poland, no cases of human infection with anisakid nematodes have been detected so far. In this study, we report the first case of gastric anisakiasis in Poland, in a 59-year-old female patient, after eating raw Atlantic salmon ( Salmo salar ). The parasite was identified as the third-stage larva of Anisakis simplex sensu stricto on the basis of morphology and molecular analysis. The larva was still alive and causing pain until it was removed, which occurred more than 5 weeks after infection. The described case prove that anisakiasis should be considered as a potential cause of gastrointestinal tract ailments following the consumption of seafood in countries where no cases of this zoonosis have been reported to date. Highlights: The first case of human anisakidosis have been detected in Poland The diagnosis was achieved by microscopic and molecular examination (PCR and DNA-sequencing) Anisakidosis should be considered in diagnostics of all gastrointestinal ailments after consumption of marine fish